ANALISIS PEMIKIRAN MUHAMMAD SYAFI’I ANTONIO TENTANG RIBA DAN BUNGA BANK - Yuliana, Nia; Harun, M; Hidayat, Fatah (Muamalah, 2018)
ABSTRACT The study is titled “Analysis Thought Muhammad Syafi'i Antonio about Riba and Interest Bank, with the background of the problem that in maintaining the benefit of human life from moral damages (morals), social, and economic then Islam firmly and definitely forbid usury. However, as the times progressed, Muslims began to be confronted with the contacts of western civilization where today's banking requires interest. Therefore, the concept of usury that is considered the final legal status began to undergo a review by Islamic reformers such as Muhammad Syafi'i Antonio. The problem raised in the writing of this thesis is how the thought of Muhammad Syafi'i Antonio about usury and bank interest, and what is the basis of the thought of Muhammad Syafi'i Antonio about usury and bank interest in Indonesian banking practices. The methodology of this study using a type of literature study (Library Reseach) which emphasizes the source of information from various materials bibliography, data collection techniques in this study is to collect data related to the thought of Muhammad Syafi'i Antonio. Then the data is analyzed by using descriptive qualitative data analysis method. Based on the result of the research, it can be concluded that Muhammad Syafi'i Antonio decided the position of bank interest and usury is the same and the law is haram, using adillat al-syari'ah (al-Qur'an and Sunnah), istinbath method of law maslahah almursalah and istihsan . Using a specific proposition and implementing general propositions as appropriate targets. As in usul fiqh rules, and economic views. Then Muhammad Syafi'i Antonio also asserted that scholars among whom A. Hasan who has justified usury, is less comprehensive in understanding and taking legal arguments. Keywords: Riba, Bank Interest, Thought, Muhammad Syafi'i Antonio.